2017
DOI: 10.3390/arts6040018
|View full text |Cite
|
Sign up to set email alerts
|

Art in the Age of Machine Intelligence

Abstract: In this wide‐ranging essay, the leader of Google’s Seattle AI group and founder of the Artists and Machine Intelligence program discusses the long‐standing and complex relationship between art and technology. The transformation of artistic practice and theory that attended the 19th century photographic revolution is explored as a parallel for the current revolution in machine intelligence, which promises not only to mechanize (or democratize) the means of reproduction, but also of production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
0
14
0
3
Order By: Relevance
“…Moreover, different results have also been found across domains of trust: for example, Rhodes et al (2013) found that judgments of sexual unfaithfulness, but not trustworthiness, were accurate in distinguishing unfaithful men. The claim that facial trustworthiness impressions are accurate is therefore debated, both in the scientific literature (Bonnefon et al, 2015; Todorov, Funk, et al, 2015) and in the public eye (Agüera y Arcas et al, 2017; Owano, 2016).…”
mentioning
confidence: 99%
“…Moreover, different results have also been found across domains of trust: for example, Rhodes et al (2013) found that judgments of sexual unfaithfulness, but not trustworthiness, were accurate in distinguishing unfaithful men. The claim that facial trustworthiness impressions are accurate is therefore debated, both in the scientific literature (Bonnefon et al, 2015; Todorov, Funk, et al, 2015) and in the public eye (Agüera y Arcas et al, 2017; Owano, 2016).…”
mentioning
confidence: 99%
“…"From today, painting is dead!" -Paul Delaroche, painter, at a demonstration of the daguerreotype in 1839 1 For lessons from the past about AI and art, perhaps no invention is more significant than photography. 2 Prior to the invention of photography, realistic images of the world could only be produced by artists.…”
Section: How Photography Became An Artformmentioning
confidence: 99%
“…The historical information from this section is distilled from two texts: Scharf[60] and Rosenblum[57] 2. This connection has been made previously[34,1], but I explore it much more thoroughly here.…”
mentioning
confidence: 99%
“…Sự thay đổi lớn sẽ nằm ở mối quan hệ giữa máy móc và con người: người nghệ sĩ không tự tay thực hiện công việc sáng tạo mà thông qua thuật toán để sáng tạo [10], hay khi máy móc có khả năng đem đến những đóng góp bất ngờ như một người đồng nghiệp [8]. Đồng thời, trí thông minh nhân tạo cũng vượt xa khỏi ranh giới của một công cụ vì nó là một dạng trí thông minh [11], và sử dụng trí thông minh nhân tạo cũng tương tự việc dạy máy móc suy nghĩ một cách nhân văn [12].…”
Section: Nguồn: Pexelsunclassified